Prior Work and Educational Experience Are Not Associated With Successful Completion of a Master's‐Level, Distance Education Midwifery Program. (13th March 2018) - Niemczyk, Nancy A.; Cutts, Alison; Perlman, Dana B.
Abstract : Introduction: In order to increase and diversify the midwifery workforce, admissions criteria for midwifery education programs must not contain unnecessary barriers to entry. Once accepted, students need to successfully complete the program. Many admissions criteria commonly used in midwifery education programs in the United States are not evidence based and could be unnecessary barriers to education. The primary objective of this study was to identify factors known during the admission process that were related to successful completion or failure to complete a midwifery program educating both student nurse‐midwives (SNMs) and student midwives (SMs); a secondary objective was to quantify reasons for program noncompletion. Methods: This master's‐level, distance education program educates a diverse group of both SNMs and SMs. A pilot, retrospective cohort study examined all students matriculating at the program from fall 2012 on and scheduled to graduate by summer 2016 (N = 58). Demographic information, admissions information, academic records, and advising notes were reviewed. Reasons for noncompletion were identified, and characteristics were compared between students who did and did not complete the program. Results: Program completion was not significantly associated with students' status as nurses prior to admission, labor and delivery nursing experience, length of nursing experience, nursing degree held, presence of children at home, working while in school, or undergraduate grade point average. Discussion: Being a nurse, years of nursing experience, type of nursing degree, or labor and delivery nursing experience were not associated with completion of this midwifery program.